Ultrasound-Derived Diaphragm Contractile Reserve as a Marker of Clinical Status in Patients With Cystic Fibrosis - Gabrysz-Forget, Fanny; Maynard-Paquette, Anne-Catherine; Kharat, Aileen; Tremblay, François; Silviet-Carricart, Maité; Lavoie, Annick; Girard, Martin; Dubé, Bruno-Pierre (Frontiers in Physiology, 2022)
Introduction In patients with cystic fibrosis (CF), the monitoring of respiratory muscle activity using electromyography can provide information on the demand-to-capacity ratio of the respiratory system and act as a clinical marker of disease activity, but this technique is not adapted to routine clinical care. Ultrasonography of the diaphragm could provide an alternative, simpler and more widely available alternative allowing the real-time assessment of the diaphragm contractile reserve (DCR), but its relationship with recognized markers of disease severity and clinical outcomes are currently unknown. Methods Stable patients with CF were prospectively recruited. Diaphragm ultrasound was performed and compared to forced expiratory volume in 1 second (FEV1), residual volume (RV), handgrip strength, fat-free mass index (FFMI), serum vitamin levels, dyspnea levels and rate of acute exacerbation (AE). Diaphragm activity was reported as DCR (the ratio of tidal-to-maximal thickening fractions, representing the remaining diaphragm contractility available after tidal inspiration) and TFmax (representing maximal diaphragm contractile strength). Inter-observer reliability of the measurement of DCR was evaluated using intra-class correlation analysis. Results 110 patients were included (61 males, median [interquartile range], age 31 [27-38] years, FEV1 66 [46-82] %predicted]. DCR was significantly correlated to FEV1 (rho=0.46, p<0.001), residual volume (rho=-0.46, p<0.001), FFMI (rho=0.41, p<0.001) and handgrip strength (rho=0.22, p=0.02), but TFmax was not. In a multiple linear regression analysis, both RV and FFMI were independent predictors of DCR. DCR, but not TFmax, was statistically lower in patients with >2 exacerbations/year (56±25 vs 71±17%, p=0.001) and significantly lower with higher dyspnea levels. A ROC analysis showed that DCR performed better than FEV1 (mean difference in AUROC 0.09, p=0.04), RV (mean difference in AUROC 0.11, p=0.03) and TFmax at identifying patients with an mMRC score >2. Inter-observer reliability of DCR was high (ICC=0.89, 95% CI 0.84-0.92, p<0.001). Conclusion In patients with CF, DCR is a reliable and non-invasive marker of disease severity that is related to respiratory and extra-pulmonary manifestations of the disease and to clinical outcomes. Future studies investigating the use of DCR as a longitudinal marker of disease progression, response to interventions or target for therapy would further validate its translation into clinical practice.